The Indonesian SMEs and Global Market Penetration: The Effects of Human Capital Investment, Government Role, and Technological Progress - Ali Mumdin; AM Soma; Ramayuli Ramayuli (Prosiding Amal Insani Foundation, 2024)
This study aims to analyze the influence of entrepreneurial orientation, human capital investment, technological transformation, and government role on the internationalization strategy of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs play a crucial role in the Indonesian economy, contributing more than half of the national income in 2019 and holding significant potential for international expansion, which is the focus of this research. Quantitative methods were employed using descriptive-verification analysis, following the footsteps of statistical pioneers like Ronald A. Fisher and Karl Pearson. The sample comprised 180 MSME exporters selected through cluster sampling. Data were collected via questionnaires using a 1-7 Likert scale, and analysis was conducted using descriptive statistics and Partial Least Squares (PLS) to test the significance of variables and their relationships in the model. The results indicate that technological transformation significantly impacts the internationalization strategy of MSMEs, while entrepreneurial orientation, human capital investment, and government role do not have strong enough effects in this context. Nevertheless, this study provides better guidance for stakeholders in supporting the growth and success of MSMEs in international markets and expanding the international market share of MSMEs to support sustainable economic growth in Indonesia. The novelty of this research lies in the simultaneous integration of four variables: entrepreneurial orientation, human capital investment, technological transformation, and government role, which has not been done before in similar studies. This adds original value by summarizing the crucial factors influencing MSMEs in Indonesia in the context of internationalization, contributing fresh insights to related literature, and enriching understanding of MSME dynamics in the Indonesian economy